IMPLEMENTING HOT SEAT GAME TO TEACH VOCABULARY AS A PART OF SPEAKING ACTIVITIES AT SENIOR HIGH SCHOOL - Gusfina Rahmawati; Desvalini Anwar (Universitas Negeri Padang, 2018)
This article aims to explain how English teachers can use Hot Seat Game to improve the students’ speaking ability at Senior High School. This Game aims to encourage students to be more active to speak English through group activities. To play this game, teacher by deviding students into several groups of 4-5 students. The teacher will choose one student to become a Hot Seat Member, and give the students questions. The questions given by the teacher can be a picture or cards that contains the words. The student who become a Hot Seat Member will guess the picture or the card without looking at it. Through Hot Seat Game, students will be encouraged to speak English to give signs to his friend who became the Hot Seat Member.